2013
DOI: 10.1016/j.ygyno.2013.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Development and pilot of an advance care planning website for women with ovarian cancer: A randomized controlled trial

Abstract: Objective Few available tools facilitate cancer patients and physicians' discussions of quality of life and end-of-life. Our objective was to develop a web-based tool to promote advance care planning for women with ovarian cancer. Methods Women with ovarian cancer, their families, clinicians and researchers met to identify ways to improve cancer care. A prototype website was created to address advance care planning, focusing on advance healthcare directives (AHD) and palliative care consultation. Patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(77 citation statements)
references
References 41 publications
3
71
0
3
Order By: Relevance
“…The authors examined an ACP workbook and found a significant increase in the discussion of ACP with health care practitioners (64% vs 28%; P < .001) and in documentation of living wills (48% vs 23%; P < .001). Finally, a poor-quality small RCT 45 tested a website to promote ACP and palliative care consultation for women with ovarian cancer. This small study found no effect of the website tool on advance directive completion or palliative care consultation.…”
Section: Resultsmentioning
confidence: 99%
“…The authors examined an ACP workbook and found a significant increase in the discussion of ACP with health care practitioners (64% vs 28%; P < .001) and in documentation of living wills (48% vs 23%; P < .001). Finally, a poor-quality small RCT 45 tested a website to promote ACP and palliative care consultation for women with ovarian cancer. This small study found no effect of the website tool on advance directive completion or palliative care consultation.…”
Section: Resultsmentioning
confidence: 99%
“…Patients progressing one SoC during the first 1 month of treatment can double their chances of action (13). The SoC model has been used in multiple disciplines to aid patients in making difficult decisions about many conditions, including renal transplantation (14)(15)(16)(17)(18)(19)(20). The aims of this study were to (1) develop an SoC tool to measure patient readiness for dialysis modality decision-making, (2) determine associations between SoC and dialysis modality decision-making, and (3) determine additional factors associated with both SoC and dialysis decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…Dans une étude australienne, la tenue d'un cahier de suivi des marqueurs améliore la communication entre le médecin et la patiente [16]. L'amélioration des connaissances des patientes sur leur maladie et leurs traitements passe sans doute aussi par la remise de documents écrits, comme le demandent nos patientes, au travers de guides pratiques disponibles dans leur centre de soins ou sur internet, comme le montrent des expériences parfois anciennes [17] ou plus récentes [18]. En France, les moyens disponibles sont multiples : guide ecancer, dispositif d'IDE d'annonce pour la répétition des informations et la vulgarisation des propos médicaux, documents remis avec les informations sur les effets secondaires, les guides destinés au patient de l'ESMO ou édités par l'INCa, ainsi que de multiples documents réalisés par les services de soins oncologiques.…”
Section: Discussionunclassified